Stereoselective synthesis of the key intermediate of ticagrelor and its diverse analogs using a new alcohol dehydrogenase from Rhodococcus kyotonensis. (May 2020) - Hu, Junmei; Li, Gudong; Liang, Chaoqun; Shams, Saira; Zhu, Shaozhou; Zheng, Guojun
Graphical abstract: Highlights: Discover a novel alcohol dehydrogenase (Rhky-ADH) from R. kyotonensis. First enzyme from Rhodococcus for synthesis of key ticagrelor intermediates. Rhky-ADH exhibited notable activity towards several aryl ketones. Abstract: Bioreduction catalyzed by alcohol dehydrogenase/reductase is one of the most valuable biotransformation processes widely used in industry. The ( S )-2-Chloro-1-(3, 4-difluorophenyl) ethanol is a key chiral synthon for synthesizing the antithrombotic agent ticagrelor. Herein, a new alcohol dehydrogenase (named Rhky-ADH) identified from Rhodococcus kyotonensis by an enzyme promiscuity-based genome mining method was successfully cloned and functionally expressed in Escherichia coli . The whole cell biocatalyst harboring Rhky-ADH was biochemically characterized and was shown to be able to convert 2-Chloro-1-(3, 4-difluorophenyl) ethanone to ( S )-2-Chloro-1-(3, 4-difluorophenyl) ethanol with more than 99 % enantiomeric excess (ee) and 99 % conversion. Our data showed that the optimum temperature and pH for Rhky-ADH were 25 °C and pH 8.0, respectively. The addition of NADH and an appropriate concentration of isopropanol enhanced the activity of Rhky-ADH, and 1 mM Mn 2+ increased the enzyme activity by about 8 %. Substrate specificity experiments showed that Rhky-ADH had notable enzyme promiscuity and could reduce several ketones with high stereoselectivity. Our investigation on this novel enzyme adds another rare biocatalyst to the toolbox for producing chiral alcohols, which are widely used in the pharmaceutical industry.